Determinación de la temperatura de secado para la encapsulación de proteasa mediante secado por atomización (2016)
Encapsulation is a technique by which substances are introduced to an array or wall system with the goal of avoiding their loss due to environmental, processing and gastrointestinal conditions to which they are generally subjected, however during this process, it is necessary to take into account the conditions under which it is carried out, in other words the concentration of coating material and the drying temperature used, in order to in this way obtain capsules with the required characteristics. Taking this into account, the optimal drying temperature is determined for the encapsulation of liquid alkaline protease enzyme DT-ZYME L 500 (Proenzimas, Colombia) at 1%, performing encapsulation by spray drying using different entry temperatures (80, 90, 100, 110, 150 °C), an exit temperature of 40 °C and a maltodextrin concentration of 50%. The performance, particle size, water activity (aw) and humidity content (CH) of said treatments were evaluated. The results showed performances of 3.83, 10.30, 12.82, 8.91 and 7.58% for treatments 1, 2, 3, 4 and 5 respectively, as well as particles sizes between 22.98±3.67 and 101.21±47.92, humidity content percentages between 5.55±0.06 and 6.66±0.03, and water activity between 0.024±0.001 and 0.053±0.001.